Examining market trends in the United States smokeless tobacco use: 2005–2011 - Delnevo, Cristine D (2012)
BACKGROUND: While cigarette consumption in the USA continues to decline, promotion for and consumption of smokeless tobacco (SLT) is growing. However, little research has explored what product features are driving SLT growth, despite awareness that product-level factors may be important in SLT use. This study analyses national sales data to better understand the impact of product features on SLT sales. METHODS: Data on sales of SLT in US convenience stores from 2005 to 2011 were obtained from Nielsen Research Company. Each listed product was coded for attributes such as type, brand, flavouring and form to calculate their respective total sales, market share and contribution to overall SLT growth. RESULTS: Sales of moist snuff products (including snus) increased by 65.6% between 2005 and 2011. Sales of pouched and flavoured forms of moist snuff increased by 333.8% and 72.1%, respectively, and contributed to 28% and 59.4% of the total growth in the moist snuff category, respectively. Value/discount brands accounted for 42% of moist snuff sales in 2011 among the top 10 selling brands, largely driven by Grizzly. After 2 years on the national market, Camel Snus was also one of the top 10 selling moist snuff brands. CONCLUSIONS: Sales of moist snuff, both overall and for particular styles, are increasing. Growing pouch use may be attributed to new SLT users, which may include cigarette smokers using them as starter SLT products. Increased sales of flavoured and discounted snuff raise concerns about use and appeal to youth. Continued surveillance of SLT sales trends is warranted.